Developmentally Programmed Division of Labor in the Aquatic Invader Alternanthera philoxeroides Under Homogeneous Soil Nutrients - Xi, Dao-Guo; You, Wen-Hua; Hu, An-An; Huang, Ping; Du, Dao-Lin (Frontiers in Plant Science, 2019)
Clonal traits can contribute to plant invasiveness, but little is known about the roles of division of labor (a key clonal trait) in homogeneous habitats. The hypothesis tested is that clonal integration allows division of labor and increases the overall performance of an invasive clonal plant, especially under higher soil nutrients. Clonal fragment pairs of aquatic invader Alternanthera philoxeroides (each with four ramets and a stolon apex) were grown in two homogenous habitats with high or low soil nutrient supply, and with stolon connections being either severed (clonal integration prevented) or kept intact (clonal integration allowed). Results showed that stolon connection allowed the division of labor within the clonal fragment, with basal ramets specializing in acquisition of belowground resources and apical ramets specializing in acquisition of aboveground expansion. Moreover, the capacity for division of labor was greater, which brought the clonal fragments of A. philoxeroides stronger clonal propagation and better performance in high nutrient habitats than in low nutrient habitats. The results supported our hypotheses that the developmentally programmed division of labor may facilitate the clonal expansion of this aggressive invader in some homogeneous habitats with high resource availability.